Implementation of the Cooperative Integrated Reading and Composition (CIRC) Learning Model to Improve the Reading Comprehension Ability of Class IV Students at SDN Krenceng I - Afrizal, Muhamad; Yuliana, Rina; Rokmanah, Siti (CV. Rayyan Dwi Bharata, 2025)
The ability to read comprehension is a process in which abilities or skills must be developed in order to increase students' insight with knowledge and information related to reading which will later be developed. The CIRC model is a learning method that uses plans and texts. Students work in pairs to read and summarize. The general objective of this research is to understand the process of implementing the Cooperative Integrated Reading and Composition (CIRC) learning model to improve the reading comprehension skills of class IV students at SDN Krenceng I. This research chooses a quantitative approach with a research method, namely, quasi-experimental research. The design used by researchers in their research is Nonequivalent Control Group Design. The sample selection in this research was 27 students in class IV of SDN Krenceng I for the 2024/2025 academic year. Pre-Test data shows that the Experiment class and Control class in literacy learning on students' reading comprehension abilities are still low. In the experimental class, the average score was 65.07 so that in this category the students were quite good at reading comprehension skills. Meanwhile, in the control class, the average score was 57.75 so that the category of students' reading comprehension ability was quite good.